The Utilization of Authentic Materials in Indonesian EFL Contexts: An Exploratory Study on Learners` Perceptions - Heri Mudra (Universitas Negeri Padang, 2014)
The purposes of this study were to find out the kinds of preferred authentic materials (AMs) utilized by EFL learners at Islamic State College of Kerinci (STAIN Kerinci), Indonesia; and, to explore the learners` perceptions on the utilization of preferred AMs in EFL classrooms. This study was carried out of phenomenological approach by employing focus-group interviews towards seven learners selected by using purposive sampling technique. The findings of the study show that the EFL learners utilize various kinds of AMs including internet-mediated AMs, printed AMs, audiovisual (video) AMs, and audio AMs. Based on the learners, each kind of materials has either advantages or disadvantages. The advantages of AMs are improving and developing skills or abilities on listening, reading, speaking, writing, vocabulary, grammar, and pronunciation. The materials also make the learners aware of the importance of native-speaker cultures through which real English is learnt. However, the disadvantages of AMs are unlimited in length and lack of academic instructions. The problems are solved by adapting each material based on EFL learners` levels and by providing instructions for each AMs. EFL teachers are to provide various AMs for EFL classrooms. The AMs should be selected and balanced with EFL learners` English abilities or levels.